2017
DOI: 10.1007/s00894-017-3273-4
|View full text |Cite|
|
Sign up to set email alerts
|

First hyperpolarizability of cyclooctatetraene modulated by alkali and alkaline earth metals

Abstract: In the present investigation, the first hyperpolarizability of alkali and alkaline earth metal derivatives of cyclooctatetraene (COT) has been calculated using BHHLYP and CAM-B3LYP functional for 6-311++G(d,p), 6-311++G(3df,3pd), and aug-pc 2 basis sets. Introduction of Na/K atoms at the axial position of COT and Li, Na, K/Be, Mg, Ca metal atoms and cyanide groups at the equatorial sites leads to lager enhancement of first hyperpolarizability. The ring charge density can account for the variation of first hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…64 Amongst the chosen DFT functionals, the CAM-B3LYP method has been employed extensively in calculating the first hyperpolarizability 65 of various kinds of molecular systems. This range separated functional also gives satisfactory results 39,48,66 of first hyperpolarizability obtained for alkali and alkaline earth metal doped organometallic systems. Champagne et al 67 showed that the hybrid functional BHHLYP minimizes the overestimation of NLO properties.…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…64 Amongst the chosen DFT functionals, the CAM-B3LYP method has been employed extensively in calculating the first hyperpolarizability 65 of various kinds of molecular systems. This range separated functional also gives satisfactory results 39,48,66 of first hyperpolarizability obtained for alkali and alkaline earth metal doped organometallic systems. Champagne et al 67 showed that the hybrid functional BHHLYP minimizes the overestimation of NLO properties.…”
Section: Methodsmentioning
confidence: 54%
“…58 The range separated CAM-B3LYP functional has been popularly used in time dependent excited state calculations for alkali/alkaline earth metal-organic complexes. 27,39,48,71 BHHLYP 69,72 and wB97XD 73 functionals have also been successfully employed in the TD-DFT calculation of the spectroscopic properties of organometallic systems involving alkali and alkaline earth metals. In view of this, the XC functionals CAM-B3LYP, BHHLYP and wB97XD are considered in conjunction with the 6-311++G(d,p) basis set in the present TD-DFT calculations of spectroscopic parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the basis set, the polarization consistent group of basis sets of Jensen,the aug-pc2 [57] is considered for this work (this basis set is augmented with diffuse functions) for evaluating the isotropic polarizability as well as the non-linear hyperpolarizability. Due to the presence of extra diffuse set of function, this basis set has been extensively used for evaluating the hyperpolarizability [58]. Along with it, the 6-311++G(3df,3pd) and 6-311++G(d,p) basis set have been employed for all the chosen DFT functionals.Here, we have computed frequency-dependent second hyperpolarizability, the electro-optic Kerr effect ( (-ω;ω,0,0)) and the electric-field induced second harmonic generation (ESHG)( (-2ω;ω,ω,0)) using different frequencies, ω= 0.001-0.004 and evaluated the change in non-linear refractive index with the change of frequency.…”
Section: Computation Detailsmentioning
confidence: 99%
“…This above functional has been widely used for evaluating the electronic property of diffuse electron systems. [64,10,58] The TD-DFT calculations of aziridine derivatives are also carried out using the aforementioned functional [45].The variation of static second hyperpolarizability along zzzz axis can be explained by the spectroscopic parameter using thetwo state model [65]. 24…”
Section: Variation Of Polarizability and Second Hyperpolarizabilitymentioning
confidence: 99%